Literature as an infra-urban mythology of evil. Sábato: “Report on the blind”, in On heroes and tombs (1961-1993 - Chaparro Amaya, Adolfo (Amaltea. Revista de Mitocrítica, 2023)
The article raises the question of the scope of the Report on the Blind, the central chapter of On Heroes and Tombs, as a phenomenal, poetic, and mythological approach to the question of evil. The first part deals with tracing the personal, moral, and aesthetic motives that lead Sabato to the formulation of the myth of the Sect of the Blind as a plausible hypothesis about the intelligibility of evil. The second explores the pictorial, cinematic, and staging resources that Sábato uses to enter the underworld, the realm of evil. The last part attempts to situate the Sábato text in the whole of his life and work as a resource for examining the metaphysical, political, and moral scope of his thought.